Is Our Self Related to Personality? A Neuropsychodynamic Model - Scalabrini, Andrea; Mucci, Clara; Northoff, Georg (Frontiers in Human Neuroscience, 2018)
The concept and the assessment of personality have been extensively discussed in psychoanalysis and in clinical psychology over the years. Nowadays there is large consensus in considering the constructs of self and relatedness as central criterions to assess personality and its disturbances. However the relation between the psychological organization of personality, the construct of self and its neuronal correlates remain unclear. Based on recent empirical data on the neural correlates of self (and others), on the importance of early relational and attachment experiences, and on the relation with the brain’s spontaneous/resting state activity (rest – self overlap/containment), we here propose a multilayered model of self with (i) relational alignment; (ii) self-constitution; (iii) self-manifestation; and (iv) self-expansion. Importantly, these different layers of self can be characterized by different neuronal correlates – this results in different neuronally grounded configurations or organizations of personality. These layers correspond to different levels of personality organization like psychotic (as related to the layer of self-constitution), borderline (as related to the layer of self-manifestation), and neurotic (as related to the layer of self-expansion). Taken together, we here provide for the first time a neurobiologically and clinically grounded model of personality organization, which carries major psychodynamic and neuroscientific implications. The study of the spontaneous activity of the brain, intrinsically related to the self (rest–self overlap/containment) and the interaction with stimuli (rest–stimulus interaction) may represent a further advance in understanding how our default state plays a crucial role in navigating through the internal world and the external reality.